2017
DOI: 10.3390/rs9040385
|View full text |Cite
|
Sign up to set email alerts
|

MBES-CARIS Data Validation for Bathymetric Mapping of Shallow Water in the Kingdom of Bahrain on the Arabian Gulf

Abstract: Sound navigating and ranging (SONAR) detection systems can provide valuable information for navigation and security, especially in shallow coastal areas. The last few years have seen an important increase in the volume of bathymetric data produced by Multi-Beam Echo-sounder Systems (MBES). Recently, the General Bathymetric Chart of the Oceans (GEBCO) released these MBES dataset preprocessed and processed with Computer Aided Resource Information System (CARIS) for public domain use. For the first time, this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…In addition to the relative SDB obtained from the ln(blue)/ln(green), additional two band ratios (ln(blue)/ln(red) and ln(green)/ln(red)) were calibrated to the local datum, as expressed in Equations (9) and (10) The common use of blue and green ratio in absolute SDB studies is based on the fact that they can penetration deeper in the water and hence allows offshore bathymetry mapping, which can reach 30 m in very clear water. However the use of blue and red band ratio in shallow turbid water can provide more precise water depth information due to the water reflectance in red enhanced by the presence of sediment particles, normally absorbed by clear water.…”
Section: Obra Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the relative SDB obtained from the ln(blue)/ln(green), additional two band ratios (ln(blue)/ln(red) and ln(green)/ln(red)) were calibrated to the local datum, as expressed in Equations (9) and (10) The common use of blue and green ratio in absolute SDB studies is based on the fact that they can penetration deeper in the water and hence allows offshore bathymetry mapping, which can reach 30 m in very clear water. However the use of blue and red band ratio in shallow turbid water can provide more precise water depth information due to the water reflectance in red enhanced by the presence of sediment particles, normally absorbed by clear water.…”
Section: Obra Methodsmentioning
confidence: 99%
“…Accurate and reliable bathymetry information is important for coastal erosion studies, maritime navigation, the mapping and monitoring of benthic habits, dredging planning, and coastal management in general. Traditional methods for bathymetry surveys use boats and ships equipped with multi-beam echo sounder or single beam echo sounder [9,10] or topo-bathymetry Lidar [11,12]. Such methods are able provide accurate water depth information; however, they are expensive and inefficient in hard-to-reach shallow waters [13].…”
Section: Introductionmentioning
confidence: 99%
“…Niu et al [26] used the feed-forward neural network (FFNN) and support vector machine (SVM) classifiers to infer ship location from acoustical data in a deep waterway channel. Bannari et al [27] suggested an approach for bathymetric mapping of shallow water of Arabian Gulf near Bahrain using the kriging procedure. Kim and Lee [28] proposed the ship traffic extraction neural network (STENet) to forecast the maritime traffic of the caution area, which represented an increased risk for ships, due to things such as berth limitations.…”
Section: Related Workmentioning
confidence: 99%
“…Traditionally, active remote sensing methods, such as ship-borne multi-beam echo sounder (MBES) and airborne light detection and ranging (LiDAR), have achieved accurate bathymetry results (Calder and Mayer 2003;Van Son et al 2009;Kennedy et al 2014). However, these conventional methods are very expensive, time-consuming, often require special permissions to work in sensitive coastal areas, and, in the case of MBES, inapplicable to shallow waters (e.g., Gao 2009;Monteys et al 2015;Bannari and Kadhem 2017).…”
Section: Application 3 Complementary Multi-platform Coastal Bathymetrymentioning
confidence: 99%